Effects of salinity and nutrients on metabolism and growth of Ulva lactuca: Implications for bioremediation of coastal watersheds. (May 2021) - Bews, Emily; Booher, Leslie; Polizzi, Torre; Long, Christopher; Kim, Ju-Hyoung; Edwards, Matthew S.
Abstract: We studied Ulva lactuca to determine its potential for bioremediation of coastal watersheds. We cultured Ulva in orthogonal combinations of two salinities and three nutrient concentrations for six weeks, and then measured its growth, photosynthesis, chlorophyll fluorescence, nitrogen, carbon and phosphorus tissue concentrations, and carbon and nitrogen uptake pathways. Our findings show that Ulva was negatively affected by decreased salinity but these effects were ameliorated by the addition of nutrients to the water, such as would be expected from freshwater runoff during heavy rain events. Also, increased nutrients resulted in altered nitrogen (NH4 + vs. NO3 − ) and carbon (HCO3 − vs. CO2 ) uptake pathways, which can allow Ulva to retain its bloom potential even under reduced salinities. Together, our study suggests that Ulva is an ideal species to grow for the purpose of bioremediation of coastal bays and estuaries, even during storms that freshen the surface waters and increase nutrients. Graphical abstract: Schematic diagram of study's main findings. Growth, fluorescence, photosynthesis, and nutrient uptake all increased under increased nutrients, while these parameters all decreased under low salinities. However, the negative effects of low salinity were ameliorated when nutrients were added. Unlabelled Image Highlights: Low salinity negatively affected Ulva growth, photosynthesis, and nutrient uptake. Elevated nutrients ameliorated the negative effects of decreased salinity. Ulva is ideal for bioremediation of polluted waterways following rain events.